Antibiotic Susceptibility Pattern of Bacterial Isolates from Burn Infection Patients Performed By Vitik-2 Instrument (Journal of the College of Basic Education, 2022)
A total of 208 microorganisms were isolated from burn wounds of 187 patients at Al-Kindy Training and Research Hospital, Baghdad, Iraq. The results revealed that the most frequent isolate was Klebsiella pneumoniae (37.5%), followed by Pseudomonas aeruginosa (25%), Acinitobacter baumannii (13.46%), Escherichia coli (7.2%), Proteus mirabilis (5.76%), Staphyllococcus aureus (3.8%), Enterobacter aerogenes (1.9%) and Burkholderia cepacia (1.4%). While Enterobacter cloacae and Staphylococcus intermedius were (0.96 %), respectively. Finally the lowest percentage were (0.48%) for Aeromonas hydrophiliacaviae, Enterococcus faecalis, Enterococcus gallinarum and Providencia stuartii, respectively. Multidrug- resistance has emerged as an important concern in our burn unit. Ciprofloxacin and Levofloxacin were found to be the most active drugs against most of isolated bacteria, Tobramycin, Ampicillin/Sulbactam were found to be the most active drugs against Acinetobacter baumannii. While, Moxifloxacin and Tigecyclin were active against gram positive bacteria